Great People: Leonardo Da Vinci: A Man Of Great Ideas
Leonardo da Vinci, best known as the painter of the fantastic Mona Lisa, was a man of great ideas. One of the greatest artists the world has ever seen, Leonardo was also an architect, a musician, a scientist, a toy-maker and a brilliant inventor who invented a model for a flying machine nearly 400 years ago! In fact, Leonardo could do just about anything he put his mind to. He was a genius who left a permanent mark on the world of art and science.Join the curious and playful Digby and his big sister Hester as they make their way through the odds and ends at Mr Rummage's stall at Knick-Knack Market. Discover the wonderful little objects they pick up and enjoy the stories about the great people they belong to.Now they must team up with a talking snow leopard, a dotty goatelope and an injured bunny to convince the Thunder Dragon to help them save the land and its people. Will Kinlay, Pem and the Moof manage to convince the sulking dragon,and halt the march of the wicked brothers' stupefied army? Will they ever be able to find their way back to school, and their parents? Enter John Shulman's fantastic web of adventure, deceit and the continuing tussle between good and evil.